Hubungan komunikasi terapeutik perawat dengan tingkat kecemasan pasien pre operasi di RSUD Sungai Dareh tahun 2025 - Saja, costarin06; Lola Amelia; Erama erfiana (Jurnal Amanah Kesehatan, 2025)
According to WHO data in 2019, preoperative patient anxiety reaches 60-90%, the level of preoperative patient anxiety reaches 534 million people. The purpose of this study was to determine the relationship between therapeutic communication between nurses and the level of preoperative patient anxiety at Sungai Dareh Hospital, Dharmasaraya Regency in 2025. This study is a quantitative study with an analytical survey design using a descriptive approach. The research time was January 13-February 28, 2025 in surgical inpatients at Sungai Dareh Hospital with a sample of 73 people who had met the inclusion and exclusion criteria using purposive sampling techniques. Based on univariate analysis, the results were 60 (82.8%) respondents with good therapeutic communication and 73 (71.2%) respondents with mild anxiety. And based on bivariate analysis using the Chi-Square test, the results showed that there was no significant relationship between the relationship between therapeutic communication between nurses and the level of preoperative patient anxiety with a P value of 0.387 ≤ 0.05. Suggestions that are expected to add and broaden insight science on the relationship between therapeutic communication of nurses and the level of pre-operative patient anxiety Keywords: Therapeutic Communication; Anxiety